Physiotherapeutic approaches in the postoperative period of anterior cruciate ligament reconstruction: a literature review - Sousa, Rodney Ribeiro de; Moura, Ayla de Jesus; Oliveira, Dyandra Fernanda Lima de; Vale, Thamires Santos do; Oliveira, Anderson dos Santos; Silva, Tamires Mendes; Veloso Júnior, Paulo Henrique de Holanda (Brazilian Journal of Science, 2022)
One of the most common injuries worldwide is the anterior cruciate ligament (ACL) injury and the initial treatment approach for this type of injury is surgical, with physiotherapy being an auxiliary post-surgical therapy for the patient in his rehabilitation process. Thus, the objective was to identify the types of physiotherapeutic protocols used in the postoperative period of anterior cruciate ligament reconstruction. The work consists of a bibliographic review, based on data from the PubMed, SciELO and PEDro indexes, published between 2016 and 2020, in Portuguese, Spanish and English. The results showed that traditional rehabilitation associated with a protocol of whole-body vibration at the ideal frequency, rehabilitation based on objective criteria, functional electrical stimulation, the use of immediate knee mobilization, strength/neuromuscular training and supervised rehabilitation. Thus, due to the aspects presented, the rehabilitation of the postoperative period of the ACL is seen as an area that encompasses several alternatives, but which still needs to be explored.